Resting pulmonary function and artery pressure and cardiopulmonary exercise testing in chronic heart failure patients in Taiwan − a prospective observational cross-sectional study comparing healthy subjects and interstitial lung disease patients - Chuang, Ming-Lung; Sia, Sung-Kien; Chang, Kai-Wei (Annals of medicine (Helsinki), 2023)
Restrictive ventilatory defects and elevated pulmonary artery pressure (PAP) are common in patients with chronic heart failure (CHF) and those with interstitial lung disease (ILD). However, as oxyhemoglobin desaturation seldom occurs in stable CHF patients at peak exercise, we hypothesized that the pathophysiology may be different between them. This study aimed to investigate: (1) PAP and lung function at rest, (2) pulmonary gas exchange (PGX) and breathing patterns at peak exercise, (3) mechanisms of dyspnea at peak exercise in patients with CHF compared to healthy subjects and ILD patients. We consecutively enrolled 83 participants (27 with CHF, 23 with ILD, and 33 healthy controls). The CHF and ILD groups had similar functional status. Lung function and cardiopulmonary exercise tests with Borg Dyspnea Score were performed. PAP was estimated using echocardiography. Resting lung function, PAP and peak exercise data in the CHF group were compared to the healthy and ILD groups. Correlation analysis was performed to elucidate the mechanisms of dyspnea in the CHF and ILD groups. Compared to the healthy group, the CHF group had normal lung function, PAP at rest, and normal dyspnea score and PGX at peak exercise, whereas the ILD group had abnormal values compared to the CHF group. Dyspnea score was positively correlated with pressure gradient, lung expansion capabilities, and expiratory tidal flow in the CHF group (all p < 0.05), but inversely correlated with inspiratory time-related variables in the ILD group (all p < 0.05). Normal lung function and PAP at rest, and dyspnea scores and PGX at peak exercise indicated that pulmonary hypertension and fibrosis were insignificant in the patients with CHF. The factors affecting dyspnea at peak exercise were different between the CHF and ILD groups. As the sample size in this study was small, large-scale studies are warranted to confirm our findings.